How can Burundi raise its growth rate? : the impact of civil conflicts and state intervention on Burundi's growth performance - Basdevant, Olivier (IMF working paper ;, 2009)
Over the last thirty years Burundi's low economic growth has led to a significant decline in per capita GDP. The purpose of this paper is to shed light on supply-side constraints that prevented Burundi's economy from growing faster. Lack of investment, civil conflict, economic inefficiencies, state intervention in the economy, and regulatory restrictions explain a large part of the weak growth performance for the last thirty years.